A new approach for determining the R-curve in DCB tests without optical measurements. (February 2015) - De Gracia, J.; Boyano, A.; Arrese, A.; Mujika, F.
Highlights: A new analytic approach for DCB test is proposed. The procedure leads to determine crack length without optical measurements. The effect of large displacements in simple manner. Abstract: A new method for obtaining the R -curve point to point by the Double Cantilever Beam test is proposed. Besides the determination of new compliance and energy release rate equations, the analytical model presented leads to calculate the crack length for every pair of load and displacement values, without any optical measurement. In addition, a simple trigonometric approximation is proposed for the calculation of large displacement effects. The approach is checked with experimental results.